Cross-country unemployment insurance, transfers, and trade-offs in international risk sharing - Zeno Enders; David Vespermann (ZBW - Leibniz Information Centre for Economics, 2021)
We assess to which degree an international transfer mechanism can enhance consumption risk sharing as well as allocative efficiency and apply our results to a potential European unemployment benefit scheme (EUBS). Specifically, we first develop a simple model with nominal rigidities to build intuition by deriving analytical results. We then use a rich DSGE model, calibrated to the Core and the Periphery of the euro area, to quantitatively analyze the changing dynamics that a EUBS brings about. We find that a EUBS can provide risk sharing by stabilizing relative consumption as well as unemployment. Following supply shocks, however, the cross-country transfer embodied in the unemployment benefits is spent to a large degree on relatively inefficiently produced goods in the receiving countries. This renders the allocation even more inefficient by opening country-specific labor wedges further, also after government-spending shocks. Yet, since this trade-off between allocative efficiency and consumption risk sharing does not exist after certain demand shocks, the welfare effects of a EUBS depend on the cause for international unemployment differentials. A EUBS that is only active after specific shocks would therefore maximize overall welfare. Even without this feature, a EUBS would raise welfare in the Core, leaving the Periphery's welfare almost unchanged.
Keywords: F45; F44; E32; 330; Cross-country transfers; international unemployment insurance; EMUEuropean business cycles; Optimum Currency Area; Structural reforms